Association between physical activity and sedentary behavior and gestational diabetes mellitus: a Mendelian randomization analysis - Jie Gao; Jingfang Liu; Jingfang Liu (Frontiers in Endocrinology)
IntroductionThe evidence of association between physical activity (PA), sedentary behavior (SB) and gestational diabetes mellitus (GDM) remains controversial in observational studies, this study aimed to generate new hypotheses between PA, SB and GDM.MethodsOur study performed Mendelian randomization (MR) analysis to explore the effects of three types of PA (moderate physical activity (MPA), moderate to vigorous physical activity (MVPA), accelerometer-based physical activity (ABPA)), three types of SB (television watching (TV), leisure computer use (PC), driving (DR)) on GDM and the mediating effect of body mass index (BMI). The inverse variance weighted method was used for the major analysis.ResultsIn univariate MR analysis, we found that genetically predicted TV and PC among SB were associated with GDM (OR = 1.61, 95%CI 1.21-2.14, P = 0.001; OR = 0.71, 95%CI 0.51-0.98, P = 0.037), whereas DR and MP were not (OR = 1.68, 95%CI 0.21-13.3, P = 0.623; OR = 1.20, 95%CI 0.87-1.65, P = 0.271). However, no association was found between physical activity and GDM: MPA (OR = 0.40, 95%CI 0.08-2.06, P = 0.273), MVPA (OR = 0.96, 95%CI 0.58-1.57, P = 0.861), and ABPA (OR = 0.99, 95%CI 0.90-1.09, P = 0.838). Multivariate MR analysis found DM (OR = 1.64, 95%CI 1.13-2.36, P = 0.008) and that BMI was a mediating factor with a 62% mediating effect.ConclusionsThis study proposes a new hypothesis for the association between TV and GDM, which is mediated by BMI, providing evidence for reducing the risk of GDM during pregnancy by reducing television watching time.